Jenis dan Kandungan Tanin Pakan Satwa Anoa (Bubalus sp.) - M Basri; Rukmi Rukmi (Media Peternakan, 2011)
Study of kinds and tannin content of diets consumed by anoa is limited. This information is very important and necessary for anoa domestication. The aims of this research were to obtain information on kinds and tannin content of anoa diets. The research was conducted in forest of Pangi Binangga nature reserve and Lore Lindu National Park, province of Central Sulawesi in March to November 2009. Digestive content analyses method was used to study the kinds of diets consumed by anoa. Chromatography was used for tannin analysis. Results of the digestive content analysis found ten kinds of anoa diets, i.e. Ficus miquelly, Caryota mitis, Ficus ampelas, Syzigium sp., Cordia mixab, Paspalum conjugatum, Smilax leocophylla, Saccarum spontaneum, Isachne globosa and Imperata cylindrica. The proportion of the diets were 60%, 45%, 35%, 17%, 12%, 10%, 8%, 8%, 5%, and 4%, respectively. Three of six diets namely Ficus miquelly, Saccarum spontaneum and Isachne globosa contained low tannin. The tannin content of three diets was 0.34%, 0.61%, and 0.99%, respectively. It is concluded that anoa in forest prefer diets that contain low tannin, such as Ficus fruits, shoots of shrubs.